Challenges and opportunities when transitioning from in vivo gene replacement to in vivo CRISPR/Cas9 therapies – a spotlight on hemophilia. (2nd September 2022) - Segurado, Oscar G; Jiang, Ruhong; Pipe, Steven W
ABSTRACT: Introduction: Currently, a few in vivo gene replacement therapies are commercially available, with many in clinical development for the treatment of some inherited monogenic diseases. These disorders arise from mutations in genes encoding essential proteins with a well understood biological function. Wide adoption of gene replacement therapies requires solid safety and efficacy profiles with demonstrable long-term durability and cost-benefit advantages vs standard therapies. Areas covered: This expert review outlines the challenges and opportunities in treating hemophilia, including the progression from in vivo gene therapies toward in vivo gene editing, focusing on pre-clinical and emerging clinical data for gene editing and addressing the need for sustained and durable gene expression during hepatocyte proliferation when the liver is unable to maintain steady gene expression and protein production. Expert opinion: In vivo gene editing in liver tissues may be able to rescue patients younger than 18 years who are not eligible for gene replacement therapies, with hemophilia as a prime example.